Вивчення багатошарового поселення між Ходосівкою та Лісниками у 2009 р. - Готун, І.А.; Казимір, О.М. (Археологічні дослідження в Україні, 2010)
Results of the work of the Northern Expedition of the IA NASU at the multilayer settlement between Khodosivka and Lisnyky are described. Materials of mostly Early Iron Age and the second and third quarters of the 1st millennium are presented to the scientific circulation.